A glucose biosensor based on the immobilization of glucose oxidase and Au nanocomposites with polynorepinephrine. Issue 29 (28th May 2019) - Liu, Yang; Nan, Xu; Shi, Wei; Liu, Xin; He, Zi; Sun, Yanan; Ge, Dongtao
Abstract : The PNE/GOD/AuNPs@PNE/Au electrode exhibited a low Michaelis–Menten constant, a fast response to glucose, outstanding anti-interference ability and high sensitivity. Abstract : A glucose biosensor based on Au nanoparticles (AuNPs), glucose oxidase (GOD) and polynorepinephrine (PNE) was fabricated by a simple and green approach. PNE-functionalized AuNPs (AuNPs@PNE) were synthetized by the polymerization of norepinephrine (NE) onto the surfaces of AuNPs and casted on an Au electrode. After dropping a solution containing NE and GOD on the AuNPs@PNE-modified Au electrode and oxidizing the monomer NE by cyclic voltammetry, a PNE, GOD and AuNP-modified Au electrode (PNE/GOD/AuNPs@PNE/Au) was obtained. The biosensor presented high sensitivity of 35.4 μA mM −1 cm −2 to glucose in the range from 0.003 mM to 3.43 mM with a response time of less than 3 s, a detection limit of 1.34 μM at a signal/noise ratio of 3, a low Michaelis–Menten constant (6.8 mM) and outstanding selectivity as well as stability. Moreover, the sensitivity and linear detection range of the as-prepared biosensor were further enhanced by the addition of the redox mediator p -benzoquinone.